Análise mecânico-estrutural de máquinas recuperadoras de roda de caçambas baseada em modelo numérico computacional - Reuel Laborne Vieira (2024)
Bucket wheel reclaimer systems (BWRS) play a crucial role in handling ore material in mining operations. The need to develop procedures to predict the mechanical behavior of machine components and provide technical data for more efficient maintenance planning is essential for large companies in the mining sector. This work deals with the development of procedures for mechanical-structural analysis, employing finite element models, with a focus on application in bucket wheel reclaimer systems. The procedure implemented in this study has the capability to predict stress levels present in the structure, estimate fatigue life at critical points, analyze the structural stability of the machine as a whole, and assess the influence of operational parameters and characteristics on the mechanical-structural condition of the equipment. Additionally, procedures for validating the computational model are addressed, carried out through adjustments of parameters based on experimental deformation measurements. Among the adjusted parameters are the center mass position of the superstructure, forces in the boom stays, and excavation cutting forces.